Unravelling the Difference Between Men and Women in Post-CABG Survival - Schmidt, Amand F.; Haitjema, Saskia; Sartipy, Ulrik; Holzmann, Martin J.; Malenka, David J.; Ross, Cathy S.; van Gilst, Wiek; Rouleau, Jean L.; Meeder, Annelijn M.; Baker, Robert A.; Shiomi, Hiroki; Kimura, Takeshi; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Women have a worse prognosis after coronary artery bypass grafting (CABG) surgery compared to men. We sought to quantify to what extend this difference in post-CABG survival could be attributed to sex itself, or whether this was mediated by difference between men and women at the time of intervention. Additionally, we explored to what extend these effects were homogenous across patient subgroups. Methods: Time to all-cause mortality was available for 102,263 CABG patients, including 20,988 (21%) women, sourced through an individual participant data meta-analysis of five cohort studies. Difference between men and women in survival duration was assessed using Kaplan-Meier estimates, and Cox’s proportional hazards model. Results: During a median follow-up of five years, 13,598 (13%) patients died, with women more likely to die than men: female HR 1.20 (95%CI 1.16; 1.25). We found that differences in patient characteristics at the time of CABG procedure mediated this sex effect, and accounting for these resulted in a neutral female HR 0.98 (95%CI 0.94; 1.02). Next we performed a priori defined subgroup analyses of the five most prominent mediators: age, creatinine, peripheral vascular disease, type 2 diabetes, and heart failure. We found that women without peripheral vascular disease (PVD) or women aged 70+, survived longer than men (interaction p-values 0.04 and 6×10-5, respectively), with an effect reversal in younger women. Conclusions: Sex differences in post-CABG survival were readily explained by difference in patient characteristics and comorbidities. Pre-planned analyses revealed patient subgroups (aged 70+, or without PVD) of women that survived longer than men, and a subgroup of younger women with comparatively poorer survival.